Hubungan Antara Pengetahuan Dan Sikap Ibu Tentang Breastcare Pada Ibu Nifas - Rani Oktarina (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2020)
WHO and IDAI (Indonesia Pediatrician League) recommended the giving of eclusive mother’s milk for 6 months and could be continued for 2 years. The breastcare to childbirth mother was needed to be done to get exclusive mother’s milk. The purpose of the research was to know the relation between mother’s and manner about breastcare to childbirth mother in district hospital of Prabumulih in 2019. The research was analytic survey by using cross sectional approach. The population of the research was mother who did breastcare in district hospital of Prabumulih in 2019, were 68 people. By univariate analysis known that from 68 respondents, the well knowlegde respondents were 45 respondents (66,2%) and the unwell knowledge respondents were 23 respondents (33,8%). The result of univariate analysis known that from 68 respondents, the respondents who had supporting manner were 41 respondents (60,3%) and the respondents who had not were 27 respondents (39,7%). Bivariate analysis showed that the knowledge had significant relation about breastcare to childbirth mother ( p value 0,002) and mother’s manner had significant relation about breastcare to childbirth mother (p value 0,000). The conclusion of the research was the significant relation between knowledge and mother’s manner about breastcare to childbirth mother in district hospital of Prabumulih in 2019.